IMPLEMENTASI PENDIDIKAN KARAKTER PESERTA DIDIK DI SD GMIT PALIBOO - Junus ill; Yermia S.Wabang; Oni sipora Bolang (JIP: Jurnal Ilmu Pendidikan, 2024)
The implementation of character education in schools aims to shape students to have good moral values ​​and positive behavior, which will equip them to become individuals with noble character, responsibility and care for others. The implementation of character education in schools focuses on instilling moral and social values ​​that will shape students into good, responsible and integrity individuals. This is done through the integration of character values ​​in the curriculum, example from teachers, habituation of positive behavior, and involvement of parents and the community. All of this aims to create a generation that is not only academically intelligent, but also has strong character and is ready to face life's challenges. The method used in this research is a qualitative descriptive research type with data collection methods of observation, interviews and documentation. Based on the research results, there are several students who have poor character, such as behaving in a disrespectful way towards teachers or friends, such as speaking rudely, interrupting conversations, or not respecting other people's opinions. And students are often involved in physical or verbal fights with peers.